How much preoperative flexion contracture is a predictor for residual flexion contracture after total knee arthroplasty in hemophilic arthropathy and rheumatoid arthritis? - Hyun Woo Lee; Cheol Hee Park; Dae Kyung Bae; Sang Jun Song (Knee Surgery & Related Research, 2022)
Abstract Background Although total knee arthroplasty (TKA) in hemophilic arthropathy (HA) or rheumatoid arthritis (RA) can improve functional ability, the postoperative range of motion (ROM) and prosthesis durability are reduced compared with those in osteoarthritic patients. Aim We aimed to compare (1) the pre- and postoperative flexion contracture after TKA in HA and RA, (2) the threshold of preoperative flexion contracture as a predictor of residual contracture > 15° after TKA, and (3) the survival rate. Methods Data from a consecutive cohort comprising 48 TKAs in HA and 92 TKAs in RA were retrospectively reviewed. The degree of flexion contracture was analyzed. Through receiver operating characteristics analysis, we aimed to determine the cutoff value of preoperative flexion contracture that increases the risk of residual contracture > 15° after TKA and compare the cutoff value in HA and RA. The survival rate was evaluated based on life table analysis and the Kaplan–Meier method. Results The degree of preoperative flexion contracture was not significantly different. The degree of postoperative residual flexion contracture was 5.6° in the HA group and 1.4° in the RA group, respectively (p < 0.001). The cutoff value of preoperative flexion contracture for residual contracture of > 15° at last-follow up was 25.0° in the HA group and 32.5° in the RA group. The 5- and 12-year survival rates were 96% and 87% in the HA and 99% and 95% in the RA group, respectively (n.s.). Conclusions The postoperative residual flexion contracture was greater and the cutoff value of preoperative flexion contracture for residual contracture was smaller in the HA group than the RA group. Appropriate intra- and postoperative care to avoid postoperative residual contracture is required in HA patients. Level of evidence III.